(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2016)
The paper is inspired by the ‘new’ bills concerning ‘rules on informed consent and advance directives’ recently presented to the Italian Parliament. The paper aims at tracing the contours of a legislation equipped with robust legal criteria useful to make decision in the most critical health care situations whenever individuals are nearing the end of life. The paper also defines the features of such a legislation with regard to the complex interrelationship between rights, duties, and responsibilities of the actors involved. The paper marks the ideal limits within which the law ought to be framed. For this purpose, references are made to the current legal and ethical framework and to ‘secularism’, which is the supreme principle of the Italian legal order, as stated by the Constitutional Court in 1989.